Perancangan dan Implementasi Sistem Pola Berjalan Pada Robot Humanoid Menggunakan Metode Inverse Kinematic - Riko Andianto; Rizal Maulana; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Robot is a very important work for the life of modern humans currently. Robot created to facilitate human activities daily, especially humanoid robot, the robot is able to similar almost all human activities completely, ranging from robots have joints to robots that are able to walk and exercise, but the constraints are often seen in the humanoid robot has not been able to walk Well, therefore this study aims to obtain the error value and maximum results in the process running on humanoid robot using kinematic inverse method. This study will provide an overview of the process of walking in detail and the calculation of the value of each joint so that the robot is able to stand and walk properly. The humanoid robot research design uses actuators in the form of Dynamixel AX-12 servo motor as propulsion and minicomputer Raspberry Pi as the brain and processor of all instructions given to the robot. Testing of this humanoid robot includes the robot's straight path, the robot oblique path and the testing time taken from the movement. Testing of robot straight path has an average rate of 92% and time 54,1 second, while the straight road has 86% accuracy and time 69,46 second.